Time‐dependent contribution of BMP, FGF, IGF, and HH signaling to the proliferation of mesenchymal stroma cells during chondrogenesis. Issue 11 (1st June 2018) - Fischer, Jennifer; Knoch, Natalie; Sims, Tanja; Rosshirt, Nils; Richter, Wiltrud
Abstract : Early loss of up to 50% of cells is common for in vitro chondrogenesis of mesenchymal stromal cells (MSC) in pellet culture, reducing the efficacy and the tissue yield for cartilage engineering. Enhanced proliferation could compensate for this unwanted effect, but relevant signaling pathways remain largely unknown. The aim of this study was to identify the contribution of bone morphogenetic protein (BMP), fibroblast growth factor (FGF), insulin‐like growth factor (IGF), and hedgehog (HH) signaling toward cell proliferation during chondrogenesis and investigate whether a further mitogenic stimulation is possible and promising. Human MSC were subjected to chondrogenesis in the presence or absence of pathway inhibitors or activators up to Day 14 or from Days 14 to 28, before proliferation, DNA and proteoglycan content were quantified. [3H]‐thymidine incorporation revealed arrest of proliferation on Day 3, after which cell division was reinitiated. Although BMP signaling was essential for proliferation throughout chondrogenesis, IGF signaling was relevant only up to Day 14. In contrast, FGF and HH signaling drove proliferation only from Day 14 onward. Early BMP4, IGF‐1, or FGF18 treatment neither prevented early cell loss nor allowed further mitogenic stimulation. However, application of the HH‐agonist purmorphamine from Day 14 increased proliferation 1.44‐fold ( p < 0.05) and late BMP4‐application enhanced the DNA and proteoglycan content, with significant effects on tissue yield. Conclusively, a differential and phase‐dependent contribution of the four pathways toward proliferation was uncovered and BMP4 treatment was promising to enhance tissue yield. Culture forms less prone to size limitations by nutrient/oxygen gradients and a focus on early apoptosis prevention may be considered as the next steps to further enhance chondrocyte formation from MSC. Abstract : In conclusion, this study demonstrates a stage‐dependent contribution of IGF‐1, FGF, and hedgehog (HH) signaling to proliferation during chondrogenesis, while bone morphogenetic protein (BMP) signaling was important throughout. Net cell proliferation was enhanced by HH‐stimulation and an enhanced cell and tissue yield was obtained by BMP4 application.